Studi Kualitas Produk dan Harga Terhadap Kepuasaan Pelanggan di Marketplace Shopee - Maria Immaculata Adhisti Prima Dewi; J. Sabas Setyohadi; Sumaryati Tjitrosumarto (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The purpose of this study was to determine the influence and contribution of product quality and price variables on customer satisfaction in the shopee marketplace. The number of samples is 109 with accidental sampling technique. Data analysis techniques using descriptive, normality test, correlation and regression. Based on all the calculation results and discussion above, it can be concluded that there is a very strong and significant influence on product quality on customer satisfaction with a contribution of 65.7%. There is a strong but not significant effect of price on customer satisfaction with a contribution of 56.34%. This means that it needs to be studied further specifically for customers who shop at the Shopee marketplace whether price is not a significant variable on customer satisfaction. The implication of this research is that those who sell goods on the shopee marketplace need to pay attention to product quality because prospective customers cannot see and feel the goods being sold directly. Only through examples or pictures.